Keeping it going: the importance of delivering interprofessional education during the COVID-19 pandemic - Sue Pullon; Belinda Westenra; Wendy Thompson; Rowena Price; Meredith Perry; Hazel Neser; Julia Myers; Caroline Morris; Miriam Mitchell; Liz Kemp; Ben Gray; Rebecca Fyfe; et al. (CSIRO Publishing, 2021)
ABSTRACT BACKGROUND AND CONTEXTGlobally, the coronavirus disease 2019 (COVID-19) pandemic has highlighted the need for better interprofessional collaboration and teamwork. When disciplines have worked together to undertake testing, deliver care and administer vaccines, progress against COVID-19 has been made. Yet, teamwork has often not happened, wasting precious resources and stretching health-care workforces. Continuing to train health professionals during the pandemic is challenging, particularly delivering interprofessional education that often uses face-to-face delivery methods to optimise interactional learning. Yet, continuing to offer interprofessional education throughout the pandemic is critical to ensure a collaboration-ready health workforce. One example is continuing the established INVOLVE (Interprofessional Visits to Learn Interprofessional Values through Patient Experience) interprofessional education initiative. ASSESSMENT OF PROBLEMEducators have not always prioritised interprofessional education during the pandemic, despite its immediate and long-term benefits. The INVOLVE interprofessional education initiative, usually delivered face-to-face, was at risk of cancellation. RESULTSA quality improvement analysis of the strategies used to continue INVOLVE demonstrated that it is possible to deliver interprofessional education within the constraints of a pandemic by using innovative online and hybrid educational strategies. Educators and students demonstrated flexibility in responding to the sudden changes in teaching and learning modalities. STRATEGIESWhen pandemic alert levels change, interprofessional educators and administrators can now choose from a repertoire of teaching approaches. LESSONSFour key lessons have improved the performance and resilience of INVOLVE: hold the vision to continue interprofessional education; be nimble; use technology appropriately; and there will be silver linings and unexpected benefits to the changes.